Modelling a strategic use of records as strategic resources in the Malaysian public sector / Mohammad Azhan Abdul Aziz - Abdul Aziz, Mohammad Azhan (2022)
Records may be used to ensure transparency, to keep individuals and organizations responsible for their acts and responsibilities, and to show that organizations have met legal or regulatory standards or accepted best practices. Organizations use documents to comply with legal, regulatory, and financial standards, as well as to safeguard their properties and rights. They help to promote a democratic society's standards of accountability and secure the rights of people. They allow governments to provide people with electronically accessible services and encourage citizen engagement through information provision and digital interaction. Record surely can be identified in most organizations but the practices of record management maybe only some of the organization is familiar with it. Hence, records ought to be overseen as a vital asset to encourage the daily function and operation of the organization. Records appear as a medium to improve the effectiveness and efficiency of the organization, it becomes a strategic resource that provides for future use. This study aims at describing how public records are managed and used among officers in departments and ministries of the Malaysian government. The respondents and key informants engaged in this study are Diplomatic Administer Officer (PTD) from different position grades starting from grade M44 to JUSA because they are categorized as top management that acts as administer, policymaker, decision-maker, etc. in the organization. The respondents were randomly selected from twelve ministries and one department of the Malaysian public sector in Putrajaya. The study conducted is quantitative method. The data collection was conducted through three phases. The first phase involves the task of communicating with the sample ministries and departments selected for this research. The second phase involves the online data collection in form of Google Forms via WhatsApp application and electronic mail. The third phase involves follow-up action with the ministries and departments that have not respond to the questionnaires. Questionnaires containing four sections were used to collect and analyze the data. A total of 271 questionnaires were collected and only 266 were analyzed using SPSS and Smart-PLS software. Findings show that all hypotheses are accepted. Records users as found to have a significant and positive relationship with strategic use of records. Records value was also found to have a significant and positive relationship with strategic use of records same as the relationship between records user and records value. Moreover, records value is hypothesized as a mediator between records user and strategic use of records also indicate the same result. The results of the study have contributed to the development of research model and theory in using records as a strategic resource especially, in the government sector. Government servants especially PTD officers must use records as one of the strategic resources in carrying out their daily affairs. Systematic record management needs to be further strengthened to ensure that the preserved memory of corporate enemies contributes to the development of a developed and rapid nation.